Pengaruh Rasio Keuangan, Ukuran Entitas, dan Ukuran KAP Terhadap Audit Report Lag - D.E. Fitriana; Syaiful Bahri (Politeknik Ganesha Medan, 2022)
This study aims to determine and analyze the effect of profitability, solvency, liquidity, entity size, and KAP size on audit report lag (ARL). ARL is the length of time it takes from closing the books until the independent auditor's report is signed by KAP. The research population is trade, service and investment sector entities listed on the Indonesia Stock Exchange for the period 2017-2019. Non-probability sampling technique with purposive sampling method with a total of 51 entities. The data analysis technique is multiple regression analysis. The results show that profitability has a significant negative effect on audit report lag, meaning that high profitability will shorten the length of audit reporting time. Solvency, liquidity, entity size, and KAP size variables have no effect on audit report lag.